Interpersonal Communication Relationship of Parents with the Motivation to Learn Public Elementary School Students in Sungai Penuh City - Oktarina, Yolanda; Prayogo, Dani; Ali, Hapzi; Rafki, Rafnelly; Nofriadi, Nofriadi; Lestari, Rinda; Yani, Ahmad; Fitria, Lailani; Khotimah, Khusnul (Dinasti International Journal of Management Science, 2024)
Communication is the process by which two or more people exchange information with each other, which in turn will arrive at a deep mutual understanding (Hafied cangara 2017). Man is inseparable from the process of communication, because man is a social creature and always needs others in his life. Communication in the family is one that affects the life circumstances of each family member, because the education carried out in the family environment by parents to their children is reflected through communication activities that take place face-to-face between parents and children. The purpose of this study was to determine the relationship between parents' interpersonal communication with the learning motivation of elementary school students in Sungai Penuh city. This type of research is a correlational descriptive researcher with a quantitative approach. The study used a survey method by distributing questionnaires to the object of research as many as 100 respondents who were elementary school students in Sungai Full city. The sampling technique used is the simple random sampling quota technique. Social integration theory is used to analyze research. The data analysis used was linear regression analysis There was a relationship between parents' interpersonal communication and student learning motivation, with a relationship of 22.5%. The regression coefficient x is 0.614. That is, every addition of 1 value of interpersonal communication, the value of learning motivation increases by 0.614.